Associations between conflictual relationships, psychopathology, and the use of psychotropic drugs among older people living in residential facilities. Issue 1 (27th January 2016) - Scocco, Paolo; Toffol, Elena; Frasson, Alberto; Cavrini, Giulia; Argentino, Paola; Azzarito, Caterina; Federici, Stefano; Putzu, Paolo F.; de Girolamo, Giovanni
Abstract: Background: Psychiatric symptoms and conflictual relationships (CR) may negatively affect the delivery of care in residential facilities (RF). This study aims to analyze neuropsychiatric symptoms, their correlations with CR among older people living in RF, and their associations with the prescription of psychotropic drugs. Methods: A total of 1215 RF residents in five Italian regions were selected for this cross‐sectional study. Psychiatric symptoms and CR were assessed with the Neuropsychiatric Inventory and the Resident Assessment Instrument, respectively. Associations between Neuropsychiatric Inventory items, CR, and the use of psychotropic drugs were tested via multiple logistic regressions. Results: About half (52.7%) of the RF residents experienced one or more clinically relevant neuropsychiatric symptoms. At least one category of CR was reported for 223 residents (19%). Although reciprocal associations were found between different categories of CR, only conflictuality with other residents was associated with the use of antipsychotics (odds ratio (OR) = 2.12). Significant associations were found with irritability (with staff: OR = 2.35; with relatives: OR = 3.09), aberrant motor behaviour (with staff: OR = 2.02), and elation (with relatives: OR = 10.55). Conclusions: Neuropsychiatric symptoms and CR are common among RF residents and are reciprocally associated. Further research with longitudinal design is needed to better understand this relationship.